Maximizing the Potentials of the Internet in Enhancing the Conduct of Computer-Based Tests for University Admission in a South-West Nigerian University - Ojo, Olayinka Anthony; Akpalaba, Immaculata Ogechi; Olugbade, Damola (International Journal of Humanities and Education Development (IJHED), 2023)
The internet presents numerous opportunities for universities to reach a wide audience with timely and relevant information. This study examines the potential impact of the internet on reaching university admission candidates, identifying application challenges, and assessing the conduct of Post Unified Tertiary Matriculation Examination (Post-UTME) tests in a South-West Nigeria University. The population for the study comprised applicants who took the Post-UTME test at the Computer-Based Test (CBT) Centre, University of Medical Sciences, Ondo. The study utilized internet adverts and surveys to disseminate information and gather feedback from participants. Results showed that the majority of applicants were reached through internet digital adverts with no difficulties encountered during the application process. The university's Facebook page had the highest views and engagements from admission seekers. The conduct of the Post-UTME test was commended by most applicants. The study concluded that the Internet can facilitate increased participation and easy assessment of Post-UTME tests in the university. It recommends that universities should explore the potential benefits of internet adverts and surveys in disseminating admission-related information, extracting feedback from stakeholders, and sensitizing the public about university programs.